2002
DOI: 10.1124/dmd.30.7.778
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of a Thiazole Benzenesulfonamide Derivative, a Potent and Selective Agonist of the Human β3-Adrenergic Receptor, in Rats: Identification of a Novel Isethionic Acid Conjugate

Abstract: (1) is a potent and selective agonist of the human ␤ 3 -adrenergic receptor. We report herein the data from studies of the metabolism and excretion of 1 in rats. Five metabolites were identified in the bile of male SpragueDawley rats administered 3 H-labeled 1 by either oral gavage (10 mg/kg) or intravenous injection (3 mg/kg). These included a pyridine N-oxide derivative (M2), a primary amine resulting from N-dealkylation and loss of the pyridinyl-2-hydroxyethyl group (M4), a carboxylic acid derived from N-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The taurine conjugate, M19, was detected in bile and is likely derived from M7 which contains an aliphatic carboxylic acid that is available for conjugation with taurine. Carboxylic acid containing drugs, such as, diclofenac (Stierlin et al 1979) or metabolites (Tang et al 2002) can become conjugated with taurine.…”
Section: Discussionmentioning
confidence: 99%
“…The taurine conjugate, M19, was detected in bile and is likely derived from M7 which contains an aliphatic carboxylic acid that is available for conjugation with taurine. Carboxylic acid containing drugs, such as, diclofenac (Stierlin et al 1979) or metabolites (Tang et al 2002) can become conjugated with taurine.…”
Section: Discussionmentioning
confidence: 99%
“…dose into the feces of bile duct-cannulated rats suggested that 1 underwent efflux from the gastrointestinal tract. Since 1 has been identified as a substrate for P-glycoprotein (Tang et al, 2002), it is likely that efflux into the gastrointestinal tract was mediated by this transporter.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolite profile was determined in bile collected from rats dosed orally with 1. The metabolites that were identified were primarily hepatic oxidation products and included the pyridine N-oxide derivative, a primary amine resulting from N-dealkylation and loss of the pyridinyl-2-hydroxyethyl group; a carboxylic acid derived from N-dealkylation and loss of pyridinyl-2-hydroxyethylamine; and the corresponding taurine and isoethionic acid conjugates (Tang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In general, taurine conjugation is perceived to be a high-affinity, low-capacity system (Mulder, 1990), whereas conjugation with glucuronic acid is considered to be a highcapacity process with broad substrate specificity (Hutt and Caldwell, 1990). In the case of a ␤ 3 -adrenergic receptor agonist, Tang et al (2002) postulated that preferential conjugation by taurine or isethionic acid was observed as a result of the limited availability of the precursor carboxylic acid metabolite. In their study, direct in vivo administration of the carboxylic acid metabolite to rats at higher concentrations led to a combination of amino acid and glucuronic acid conjugation.…”
Section: Discussionmentioning
confidence: 99%